DEVELOPING BARCORIOUS BASED ANDROID APPLICATION TOWARD EYLS’ ENGLISH VOCABULARY MASTERY: FOCUS ON DESIGN - Arimuliani Ahmad; Muhammad Ilyas (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2018)
It is a big challenge for educator especially for elementary level to stimulate young students to learn English joyful. Vocabulary mastery is the basic concern to be enhanced as spoken an also written. But, the phenomenon is most of students have lack of motivation to learn especially English subject. Many factors influence it which comes from students’ side or teachers’ side such as conventional teaching method and media. As teacher and also scientist, we are called to give contribution to education field to develop an appropriate teaching media for millennial era as now. It is Barcorious Android Application (BAA) which provides audio and visual content which facilitated students’ curious and learning by doing method. There were six stages have been passed to develop this BAA such as need analysis stage, design stage, implementation stage, coding stage, testing stage and packaging stage.